Hybrid Flexible NFC Sensor on Paper - Conti, Silvia; Nepa, Francesco; Pascoli, Stefano Di; Brunetti, Irene; Pimpolari, Lorenzo; Song, Xiuju; Parvez, Khaled; Lomeri, Hamed Javanbakht; De Rossi, Francesca; Lucarelli, Giulia; Polino, Giuseppina; Brown, Thomas; et al. (IEEE journal on flexible electronics, 2023)
Everyday healthcare objects have become the focus of interdisciplinary research lines, which aim to monitor human biomedical parameters by means of ergonomic and, ideally, environmentally sustainable sensors. Here, a hybrid system, based on both solution-processed- and conventional silicon-technology, is reported. In particular, a strain and a pH sensor are developed based on graphene inks, while a humidity detector is implemented using a poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS). The printed sensors are integrated into a demonstrator consisting of a silicon near field communication (NFC) transponder chip with logic and transceiver capabilities, bonded on a circuit board with inkjet-printed components on a paper substrate: an antenna and a power supply (in addition to the sensor). This proof-of-concept seeks to address the needs for a future circular economy, as well as those for cheap, flexible, and lightweight, multi-functional electronics.